Fatigue, pain and faecal incontinence in adult inflammatory bowel disease patients and the unmet need: a national cross-sectional survey - Ailsa Hart; Laura Miller; Fionn Cléirigh Büttner; Thomas Hamborg; Sonia Saxena; Richard C. G. Pollok; Imogen Stagg; Vari Wileman; Qasim Aziz; Wladyslawa Czuber-Dochan; Lesley Dibley; Borislava Mihaylova; et al. (BMC Gastroenterology)
Abstract Background and Aims The co-existence of fatigue, pain and faecal incontinence in people with Inflammatory Bowel Disease (IBD) is unknown. We aimed to determine the presence of and relationship between these symptoms and patients’ desire for intervention. Methods Adults with IBD in the UK, recruited from clinics, the national IBD-BioResource, a patient charity and social media sources, completed PROMIS validated patient-reported questionnaires to identify fatigue, pain and faecal incontinence, in addition to symptom severity and impact, disease activity, anxiety and depression questionnaires and questions about their desire for help with these symptoms. Statistical analysis used descriptive statistics to report presence of symptoms and Pearson correlation coefficients were calculated. Results Of 8486 responses, 54% reported faecal incontinence, 24% reported fatigue, and 21% reported pain; 10% reported all three symptoms in the past 7 days. Only 29% reported none of these symptoms. Fatigue and pain were moderately correlated (Pearson correlation coefficient 0.57); both fatigue and pain had a lower correlation with faecal incontinence (0.43 and 0.46 respectively). On a 0–10 scale for severity, participants scored fatigue highest, followed by incontinence then pain. For impact, participants scored incontinence highest, followed by fatigue then pain. 56% reported depression (27% with clinically relevant levels) and 49% reported anxiety (20% with clinically relevant levels); 23% had previously medically diagnosed mental health disorders. 56% of respondents “definitely” wanted help for fatigue; 53% for incontinence; 42% for pain; 29% “definitely” wanted help with all three symptoms. Factors associated with all three symptoms were Crohn’s disease (vs. ulcerative colitis), IBD activity, IBD Control score, anxiety, depression, and history of surgery (all p ≤ 0.0001). Conclusions Fatigue, pain and incontinence are common in IBD and patients desire help for these symptoms, currently a substantial unmet need. Anxiety and depression are common, are underdiagnosed, and are independently associated with these symptoms.